Tourism Development Index of local self-government units: The example of Croatia - Opačić, Vuk Tvrtko; Klarić, Zoran; Beroš, Ivo; Boranić Živoder, Snježana (Acta geographica Slovenica, 2022)
The goal of the research was to construct a model for calculating the Tourism Development Index (TDI) at the local level. TDI is based on ten indicators: total number of beds, total number of beds per 100 residents, number of beds in hotels and similar establishments, number of beds in hotels and similar establishments per 100 residents, number of tourist arrivals, number of tourist arrivals per capita, number of overnight stays, number of overnight stays per capita, number of employed in tourism and hospitality and share of employed in tourism and hospitality in total employment. Based on TDI, 556 cities/towns and municipalities were categorised into five classes. Due to the usage of both absolute and relative values, TDI recognises the tourism development better than the previously used indices.